THE INFLUENCE OF FINANCIAL LITERACY AND SPENDING HABITS ON SHOPPING DECISIONS IN MARKET WITH PERSONAL PREFERENCE AS A MODERATION VARIABLE - Firdaus, Arsy Maulana; Hermawan, Sigit (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine the impact of financial literacy and spending habits on consumer decision-making in the marketplace. Method: The research uses a quantitative method and a sample of 115 students from the Spring 2020 semester at the University of Sidoarjo. The data analysis technique used is purposive sampling, using validity and reliability tests, a paired-probability hypothesis, and SPSS version 26 statistical software. Results: The results show that financial literacy positively influences consumer decision-making, while spending habits negatively influence consumer decision-making. Novelty: The study suggests that financial literacy can moderate the relationship between financial literacy and consumer decision-making, and that good financial management can positively influence consumer decision-making.